Opioid overdose or other somatic comorbidity - fatal case - Simonovska, Natasha; Bekjarovski, Niko; Petkovska, Lidija; Pereska, Zanina; Babulovska, Aleksandra; Kostadinoski, Kristin; Ristova, Biljana (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2024)
The aim of this case presentation is to emphasize the diagnostic challenges that the clinicians encounter when dealing with a comatose patient and the importance of keeping a broad differential diagnostic panel in mind. Case report: A 47-year-old female patient, was brought by ambulance to the University Clinic for Toxicology in Skopje. On admission, she was comatose (GCS=5), with miotic isochoric pupils, blood pressure was 90/60 mmHg, with oxygen saturation from 85 up to 92%. Тhe obtained data from family indicated that the patient was with opioid use disorder on methadone maintenance therapy. Recently, the patient has consumed large amounts of alcohol . Тhe family's suspicion was that perhaps the new condition was caused by excessive intake of alcohol or methadone or both. In the meantime, the result of alcoholemia showed 67.0 mg/dL (value <100mg/dLlow level) and the toxicological screening in urine sample for tetrahydrocannabinol, opiates, tramadol, amphetamine, 3,4-methylenedioxy-methamphetamine, cocaine, benzodiazepines, buprenorphine was negative with mildly elevated methadone values (the patient was on methadone substitute the last 7 years). Second day on physical examination a brisk response to deep tendon reflexes of the left side of the body with apparent right hemiplegia was noted. Computed tomography of the brain was performed immediately and showed an ischemic stroke with a compressive effect on the left lateral chamber. Although it was immediately started with an aggressive treatment, after 11 days the condition of the patient deteriorated and resulted in death. Conclusion: The notable opioid prevalence, mandates that physicians maintain a high index of suspicion when dealing with a comatose patient, especially if the patient has any known history of opioid abuse. Healthcare professionals should be aware that a comatose state in a patient could be caused by either non-toxicological trigger or by toxic causes.
Keywords: alcohol; methadone; ischemic stroke; coma